Machine Learning in accounting: an introduction / Wan Mardyatul Miza Wan Tahir and Jaízah Abdul Jabar - Wan Tahir, Wan Mardyatul Miza; Abdul Jabar, Jaízah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Machine Learning is an application of Artificial Intelligence (AI) in which computers use algorithms to learn and recognise patterns. Technically, it enables systems to learn from data without having to be programmed. Machine learning was eventually incorporated into our daily lives, such as on social media. Have you noticed that when you click on an article on Facebook on a specific subject, such as property, more suggestions for articles and advertisements regarding property and related subjects appear during your Facebook browsing? This is because the system uses data, such as user browser history, to try to anticipate what you might like. Hence, by looking at the connection of machine learning's on everyday life and business operations, specifically in accounting, undoubtedly it is expected the impact of that to be greater in the future than few years back.